Spectroelectrochemistry, the future of visualizing electrode processes by hyphenating electrochemistry with spectroscopic techniques. Issue 7 (30th January 2020) - Lozeman, Jasper J. A.; Führer, Pascal; Olthuis, Wouter; Odijk, Mathieu
Abstract : Reviewing the future of electrochemistry combined with infrared, Raman, and nuclear magnetic resonance spectroscopy as well as mass spectrometry. Abstract : The combination of electrochemistry and spectroscopy, known as spectroelectrochemistry (SEC), is an already established approach. By combining these two techniques, the relevance of the data obtained is greater than what it would be when using them independently. A number of review papers have been published on this subject, mostly written for experts in the field and focused on recent advances. In this review, written for both the novice in the field and the more experienced reader, the focus is not on the past but on the future. The scope is narrowed down to four techniques the authors claim to have the most potential for the future, namely: infrared spectroelectrochemistry (IR-SEC), Raman spectroelectrochemistry (Raman-SEC), nuclear magnetic resonance spectroelectrochemistry (NMR-SEC) and, perhaps slightly more controversial but certainly promising, electrochemistry mass-spectrometry (EC-MS).